2007
DOI: 10.1002/aic.11301
|View full text |Cite
|
Sign up to set email alerts
|

A computational model for temperature and sterility distributions in a pilot‐scale high‐pressure high‐temperature process

Abstract: in Wiley InterScience (www.interscience.wiley.com).High pressure high temperature processing is a candidate food sterilization process in which heat is generated volumetrically within the food as a result of rapid pressurization to 600 MPa or higher. For commercial viability the temperature profile in the process should be as uniform as possible. A model has been developed to predict the flow and temperature fields inside a pilot scale (35 L) vessel during the pressure heating, holding and cooling stages of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 31 publications
1
92
1
Order By: Relevance
“…The rapid heating and cooling in HPT processing offers the potential for producing high-quality shelf-stable products, including improved colour, flavour, and nutrient retention [1,6,11,15] compared to traditionally thermally processed products. Despite the fact that pressure is uniformly distributed throughout the pressure vessel in HPT processing, temperature is not [7,8]. The development of temperature gradients in HPT processing is a result of the differences in compression heating of the materials involved, i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The rapid heating and cooling in HPT processing offers the potential for producing high-quality shelf-stable products, including improved colour, flavour, and nutrient retention [1,6,11,15] compared to traditionally thermally processed products. Despite the fact that pressure is uniformly distributed throughout the pressure vessel in HPT processing, temperature is not [7,8]. The development of temperature gradients in HPT processing is a result of the differences in compression heating of the materials involved, i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Such nonuniform transient temperature distributions are aggravated by any temperature mismatch of the incoming compression fluid (which may comprise up to about 20% of the vessel's volume). Various heat retention aids, including internal electrical heaters and polymeric insulating product baskets, have been proposed to counteract the cooling caused by the vessel walls, and the performance of some of these has been assessed [7][8][9]. However, the issue of temperature gradients in HPT processing is likely to remain, as it also remains in traditional thermal retort processes.…”
Section: Introductionmentioning
confidence: 98%
“…Modeling of hydrodynamic and thermal changes during HHPP has been attempted by several researchers (Hartmann 2002;Hartmann and Delgado 2002, 2004Pehl et al 2000;Otero et al 2002a, b, c;Knoerzer et al 2007;Ghani and Farid 2007b). These researchers followed a deterministic approach based on governing equations of conservation of momentum and energy, in their numerical simulation models for the high pressure process.…”
Section: Introductionmentioning
confidence: 97%
“…These researchers followed a deterministic approach based on governing equations of conservation of momentum and energy, in their numerical simulation models for the high pressure process. Knoerzer et al (2007) studied the flow and temperature fields inside a pilot scale (35 L) vessel at pressure level of 600 MPa held for 285 s. They found non-uniformity in temperature during the process and showed that this can be overcome by providing thermal insulation to the system. Ghani and Farid (2007b) carried out the numerical simulation for temperature distribution, velocity field, and pressure field during high-pressure process (500 MPa up to 1,000 s hold time) in a 300 mL vessel with liquid water and solidliquid food mixture.…”
Section: Introductionmentioning
confidence: 98%
“…This term results from the following relation (for derivation, see Knoerzer et al 2007), which is valid for isentropic processes:…”
Section: (I) Heat Transfer By Conductionmentioning
confidence: 99%